Teachers' attitudes and beliefs regarding ICT in teaching and learning in European countries. (November 2017) - Eickelmann, Birgit; Vennemann, Mario
In the debate on the integration of information and communication technologies (ICT) into schools, the beliefs and attitudes of teachers towards ICT in teaching and learning have always been regarded as central criteria for successful implementation of new technologies. In this context, a study in 2013 by the International Association for the Evaluation of Educational Achievement, IEA, provided insights into teachers' beliefs regarding ICT and showed that perceptions of the pedagogical advantages of technologies differ between countries. With regard to this finding, this paper seeks to determine whether there is a typology of teachers with different attitudes towards the potential of ICTs for learning. This question is addressed by conducting latent class analyses on a sample of teacher data from three European countries – the Czech Republic, Germany and Norway. Furthermore, the paper investigates how the use of computers by teachers varies between the groups to which these teachers can be assigned. In doing so the research reported at hand connects, arguably for the first time, representative data on teacher typologies of attitudes towards and beliefs about ICT in teaching and learning with data on computer use in schools.